Remote Work and Its Impact on Productivity and Job Satisfaction in Post-COVID North-West Nigeria - Abdulkadir Abuabdin, Abubakar; Iliyasu, Sama’ila (Minhaj International Journal of Economics and Organization Sciences, 2025)
This study examines the impact of remote work on employee productivity and job satisfaction in the post-COVID-19 era, with a specific focus on North-West Nigeria. By synthesizing existing theories and empirical studies, the research explores how remote work influences workplace dynamics in this region. Key theoretical frameworks, including the Job Characteristics Model, Maslow’s Hierarchy of Needs, and Self-Determination Theory applied to analyze the benefits and challenges of remote work. The study highlights the unique socio-economic, cultural, and infrastructural factors in North-West Nigeria, such as inadequate technological infrastructure, cultural attitudes toward remote work, and economic constraints. Through a conceptual approach, the paper proposes actionable strategies for optimizing remote work, including improving digital infrastructure, promoting flexible work policies, and enhancing employee support systems. The findings suggest that while remote work can significantly enhance productivity and job satisfaction, addressing region-specific challenges is critical for its successful implementation. The study also identifies future research directions, such as empirical validation of theoretical insights and comparative analyses between urban and rural contexts in North-West Nigeria.